The International Criminal Court And Its Major Obstacles Since Formation - Nwinkol, Barinaadaa; Kia, Bariledum (Advances in Social Sciences Research Journal, 2020)
Global quest for the prosecution of heinous crimes of concern to the international community as a whole especially genocide, war crime, crime against humanity, and the crime of aggression committed by individuals led to the establishment of the International Criminal Court (ICC) on July 1, 2002. The court had however, not performed optimally due to some challenges. This paper set out to discuss the militating factors in the execution of the court’s mandate. Using the realist theory, the rational behind the attitude of India, China, Russia and the United State (all major non-state parties) in sabotaging the court’s effort is succinctly assessed. After pointing out other factors affecting the court, its way out of some of these problems was laid bare. The paper concludes that the court must make concerted efforts to replicate criminal prosecution in other parts of the world other than Africa to earn the required credibility and legitimacy it sorts. At the same time, it would have to lobby to ensure that major non-state parties, especially the United States, etc. accede to the Rome statute.